A distinct sensitivity to the priming effect between labile and stable soil organic carbon. Issue 1 (21st September 2022) - Zhang, Qiufang; Feng, Jiguang; Li, Jian; Huang, Ching‐Yu; Shen, Yawen; Cheng, Weixin; Zhu, Biao
Summary: Soil organic carbon (SOC) is a mixture of various carbon (C) compounds with different stability, which can be distinctly affected by the priming effect (PE). However, little is known about how the PE changes with SOC stability. We address this issue by combining results from two experiments and a metaanalysis. We found that the PE increased with the prolongation of soil preincubation, suggesting that higher PE occurred for more stable SOC than for labile SOC. This was further supported by the metaanalysis of 42 observations. There were significant negative relationships between the difference in PE (ΔPE) between labile and more stable SOC and their differences in SOC, microbial biomass C and soil C : N ratio, indicating that soil C availability exerts a vital control on ΔPE. We conclude that, compared with labile SOC, stable SOC can be more vulnerable to priming once microbes are provided with exogenous C substrates. This high vulnerability of stable SOC to priming warrants more attention in future studies on SOC cycling and global change.